125th Anniversary Review: Diacetyl and its control during brewery fermentation. Issue 3 (24th August 2013) - Krogerus, Kristoffer; Gibson, Brian R.
<x xml:space="preserve">Abstract</x> Diacetyl is a butter‐tasting vicinal diketone produced as a by‐product of yeast valine metabolism during fermentation. Concentration is dependent on a number of factors including rate of formation of the precursor α‐acetolactate by yeast, spontaneous decarboxylation of this acetohydroxy acid to diacetyl and removal of diacetyl by yeast via the action of various reductase enzymes. Lowering concentrations of diacetyl in green beer represents an expensive and time‐consuming part of the brewing process and strategies to minimize diacetyl formation or hasten its reduction have potential for improving overall efficiency of the lager brewing system. Here we review the processes that determine diacetyl levels in green beer as well as the various ways in which diacetyl levels can be controlled. The amount of diacetyl produced during fermentation can be affected by modifying process conditions, wort composition or fermentation technique, or by yeast strain development through genetic engineering or adaptive evolution. The process of diacetyl reduction by yeast is not as well understood as the process of formation, but is dependent on factors such as physiological condition, cell membrane composition, temperature and pH. The process of diacetyl removal is typically rate‐limited by the reaction rate for the spontaneous decarboxylation of α‐acetolactate to diacetyl. Copyright © 2013 The Institute of Brewing & Distilling